Radiological profile of patients with Cervical Spondylosis - Ajay Anirudh Jadhav; Shaik Abdul Rahim (MRIMS Journal of Health Sciences, 2016)
Background: Cervical spondylosis is a common disease of advancing age arising form the effects of a progressive degenerative changes affecting single or multiple inter vertebral disco and consequent hypertrophy, spurring and deformities of the discs and foramina. Objective: To study radiological profile of patients with cervical spondylosis Methods: A hospital based cross sectional study was carried out among 150 patients. Institutional Ethics Committee permission was obtained. From each and every patient, the informed consent was taken. A detailed history and thorough clinical examination was carried out. Data was entered and analyzed. Results: The maximum age of patient studied was 72 years, minimum age of patient studied was 16 years. Maximum patients were in 2nd and 4th decade of life. Maximum No. of cases were found in a group of sedentary workers (Doctors/Teachers/Clerks). Almost all cases present with symptom of neck pain followed by symptoms like Brachialgia, Para spinal muscle spasm, Paraesthesia. While difficulty in walking found in only 14 cases of cervical spondylosis. Conclusion: Cervical spondylosis was common in the 4th decade of life. Sedentary work was the risk factor for cervical spondylosis. Neck pain was the most common presenting symptom.